The antihelminth drug rafoxanide reverses chromosomal-mediated colistin-resistance in Klebsiella pneumoniae - Rongjia Han; Jiabao Xing; Huarun Sun; Zeyu Guo; Kaifang Yi; Gongzheng Hu; Yajun Zhai; Tony Velkov; Hua Wu (mSphere, 2023)
ABSTRACT The emergence and rapid spread of multi-drug-resistant (MDR) bacteria pose a serious threat to global healthcare. Although the synergistic effect of rafoxanide and colistin was reported, little is known regarding the potential mechanism of this synergy, particularly against chromosomal-mediated colistin-resistant Klebsiella pneumoniae. In the present study, we elucidated the synergistic effect of rafoxanide and colistin against chromosomal-mediated colistin-resistant Klebsiella pneumoniae isolates from human (KP-9) and swine (KP-1) infections. Treatment with 1 mg/L rafoxanide overtly reversed the MIC max to 512-fold. Time-kill assays indicated that rafoxanide acted synergistically with colistin against the growth of KP-1 and KP-9. Mechanistically, we unexpectedly found that the combination destroys the inner-membrane integrity, and ATP synthesis was also quenched, albeit, not via F1F0-ATPase; thereby also inhibiting the activity of efflux pumps. Excessive production of reactive oxygen species (ROS) was also an underlying factor contributing to the bacterial-killing effect of the combination. Transcriptomic analysis unraveled overt heterogeneous expression as treated with both administrations compared with monotherapy. Functional analysis of these differentially expressed genes (DEGs) targeted to the plasma membrane and ATP-binding corroborated phenotypic screening results. These novel findings highlight the synergistic mechanism of rafoxanide in combination with colistin which effectively eradicates chromosomal-mediated colistin-resistant Klebsiella pneumoniae. IMPORTANCE The antimicrobial resistance of Klebsiella pneumoniae caused by the abuse of colistin has increased the difficulty of clinical treatment. A promising combination (i.e., rafoxanide+ colistin) has successfully rescued the antibacterial effect of colistin. However, we still failed to know the potential effect of this combination on chromosome-mediated Klebsiella pneumoniae. Through a series of in vitro experiments, as well as transcriptomic profiling, we confirmed that the MIC of colistin was reduced by rafoxanide by destroying the inner-membrane integrity, quenching ATP synthesis, inhibiting the activity of the efflux pump, and increasing the production of reactive oxygen species. In turn, the expression of relevant colistin resistance genes was down-regulated. Collectively, our study revealed rafoxanide as a promising colistin adjuvant against chromosome-mediated Klebsiella pneumoniae.